The Risk-Taking Behaviour of Tunisian Banks in the Post-Revolution Era: A Panel ARDL-PMG Approach - SAADAOUI, Zied; MOKDADI, Salma (Asian Journal of Economics and Empirical Research, 2022)
This study investigates the long-term determinants of capital buffers and risk-taking adjustment by focusing on a sample of listed Tunisian commercial banks. This research uses hand-collected semi-annual data. The panel autoregressive distributed lags technique is used to control for unit root processes and to check for long-term determinants of capital and risk-taking adjustment. The empirical findings prove the existence of a moral hazard and procyclical behaviour of Tunisian banks in response to capital requirements. However, some results indicate that capital standards are still an important prudential tool for ensuring the robustness of Tunisian banks. There have been no previous studies focusing on this issue in the context of the Tunisian banking system in the turbulent post-revolution era. This paper innovates by assuming that a set of bank-specific, macroeconomic and regulatory variables exert a long-term rather than a short-term influence on capital buffers and risk-taking. The research does not consider a possible long-term simultaneous relationship between capital and risk-taking. The sample could be extended if data were available. Tunisian banks are advised to diversify their sources of revenues and to thoroughly revise their business models in order to become less dependent on revenues from traditional intermediation activities and to reduce the procyclicality of the banking system.